P114 Potassium competitive acid blocker, revaprazan, prevented indomethacin-induced intestinal permeability through tightening TJs. (16th January 2018) - Hahm, K B; Park, J M; Han, Y M
Abstract: Background: Non-steroidal anti-inflammatory drugs (NSAIDs) are the most commonly prescribed drugs for arthritis, inflammation, and cardiovascular protection. However, they cause serious gastrointestinal side effects, of which pathophysiology has mostly been originated on the cyclooxygenase (COX) inhibition and the subsequent depletion of cytoprotective prostaglandin. Furthermore, recent clinical data showed that PPI aggravated NSAIDs-induced intestinal damages through either dysbiosis or increased intestinal permeability, suggesting PPI might be no more protective against NSAID-induced intestinal damages. Methods: In this study, we investigated the changes of indomethacin (IND)-induced small intestinal damages after combination with pantoprazole (PPZ) or combination with revaprazan (REV), potassium-competitive acid blocker (PCAB). All SD rats were 5 weeks of age. After treatment after 48 h rats with indomethacin in all the groups, they were euthanized and small intestine were collected for gross and pathologic evaluation, followed by immunohistochemical staining, Western blotting for inflammatory mediators, permeability protein, and RT-PCR Results: As a result, macroscopic and histological evidences suggested that administration of IND resulted in significant intestinal damage and co-administration of PPZ resulted in worsen of IND enteropathy while attenuation of IND-induced intestinal damage in co-administration of REV. Moreover when we checked inflammatory cytokines and oxidative stress-associated factors using Western blotting and RT –PCR showed that IND with PPZ group was higher compared with IND alone group but IND plus REV group was lower compared with the PPZ group. Also we performed immunohistochemical staining to confirm intestinal permeability including ZO-1 and Occludin 1 as a result their expression was significantly decreased in IND with PPZ group, whereas no changes in IND + REV group, suggesting that PPZ aggravated IND-induced small intestinal damages, but not with REV combination. Conclusions: Thus this study in the near future that PCAB should be selected to secure NSAID-induced GI damages, while PPI should not be prescribed in this purpose.